African cassava whitefly and viral disease management through timed application of imidacloprid. (August 2022) - Omongo, Christopher Abu; Opio, Samuel Morris; Bayiyana, Irene; Otim, Michael Hillary; Omara, Tom; Wamani, Sam; Ocitti, Patrick; Bua, Anton; Macfadyen, Sarina; Colvin, John
Abstract: Cassava whitefly are a group of cryptic species within the Bemisia tabaci sensu lato complex that causes significant damage to cassava in Africa. B. tabaci Sub-Saharan Africa 1 (SSA1) is the major species in the study region which transmits plant-virus diseases to cassava and causes direct feeding damage. Benefits from management of cassava viral diseases through deployment of resistant varieties are being undermined by their susceptibility to B . tabaci SSA1 and the problem is exacerbated by high populations of B . tabaci in cassava fields. To develop a clean seed system that is disease-free, the judicious use of insecticides is required to manage this pest and vector. This study evaluated the effect of timing of insecticide application on controlling B . tabaci SSA1 population abundance and damage to cassava. Field trials were carried out between 2017 and 2018 in Kamuli and Wakiso districts of Uganda using the widely available insecticide Imidacloprid. Three cassava cultivars (NAROCASS1, SAUTI, KBH/2002/026) were planted in a randomized complete block trial design replicated three times. The insecticide was applied in split-plots designated as: (i) no protection (NP), no insecticide applied (control), (ii) early protection (EP), insecticide applied 2 times between 0 and 4 months after planting, (iii) long protection (LP), insecticide applied 3 times between 0 and 8 months after planting, and (iv) total protection (TP), insecticide applied 4 times between 0 and 12 months after planting. Except for control plots, stem cuttings were first dipped into a diluted solution of Imidacloprid prior to planting. Bi-monthly data were collected on the B. tabaci population, feeding damage, cassava mosaic disease and cassava brown streak disease. Stem cuttings and root yields were determined at harvest. The marginal rate of return for each treatment was calculated to determine cost effectiveness. Insecticide application effectively reduced B. tabaci populations, feeding damage and disease spread. Cassava yield differed significantly with insecticide treatment and amongst cultivars. Root and stem yield losses of >60% was recorded in unprotected control plots. The marginal rate of return of the early protection (0–4 MAP) program was 163%. We discuss these findings and the implication for judicious use of insecticides as part of a cassava clean seed system. Highlights: Early use of Imidacloprid followed by two foliar applications significantly reduced whitefly populations. Imidacloprid treatments resulted in low nymph densities, which prevented subsequent population build-up. Effective whitefly control by early applications of Imidacloprid reduced damage and disease incidences. Early crop protection with Imidacloprid resulted in highest tuber yields and economic benefits. This whitefly-control strategy, therefore, is viable for East African cassava growers.